A different day : African American struggles for justice in rural Louisiana, 1900-1970 - De Jong, Greta (Civil rights and social justice., 2002)
Here, the author examines African Americans' struggles for freedom and justice during the Jim Crow and civil rights eras. Using a wide range of sources, she illuminates the connections between the informal strategies of resistance in the early 20th century and the mass protests of the 50s and 60s.